2023
DOI: 10.1590/0034-7167-2022-0671
|View full text |Cite
|
Sign up to set email alerts
|

Financial toxicity in people with chronic kidney disease undergoing hemodialysis treatment

Emanuele Cristina de Sousa Silva,
Maria de Fátima Mantovani,
Luciana de Alcantara Nogueira
et al.

Abstract: Objective: to assess the financial toxicity of people with chronic kidney disease undergoing hemodialysis treatment. Method: a descriptive analytical cross-sectional study, carried out with 214 people, between February and May 2022. For data collection, a sociodemographic and clinical instrument and the COmprehensive Score for financial Toxicity were used. For analysis, the Odds Ratio, ANOVA and Cronbach’s alpha tests were used. Results: the mean financial toxicity score was 20.30. Women with a monthly famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The mean self-reported nancial toxicity score of patients was 15.25 ± 6.10. In 2022, Brazilian scholar Emanuele Cristina de Sousa Silva [19] conducted a cross-sectional survey on nancial toxicity in 214 hemodialysis patients and obtained a nancial toxicity score of 20.30 ± 8.69. Furthermore, 71% of the patients had some degree of nancial toxicity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The mean self-reported nancial toxicity score of patients was 15.25 ± 6.10. In 2022, Brazilian scholar Emanuele Cristina de Sousa Silva [19] conducted a cross-sectional survey on nancial toxicity in 214 hemodialysis patients and obtained a nancial toxicity score of 20.30 ± 8.69. Furthermore, 71% of the patients had some degree of nancial toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…This study found that age is an in uencing factor of nancial toxicity in PD patients, with older PD patients suffering less nancial toxicity. Silva's 2023 study [19] investigated the nancial toxicity of hemodialysis patients, and the results showed that 81.37% of patients aged 18-59 years had some degree of nancial toxicity, while only 62.83% of patients aged 60 years or older had some degree of nancial toxicity [19]. Yu Huihui [27] investigated the economic toxicity of Chinese adult cancer patients and found that patients who were younger than 50 years old reported signi cantly worse nancial toxicity, corroborating the results of this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have considered that in the general population, the prevalence of financial need for material, psychological and behavioral domains is around 20-50% for adults aged 18-64 years and around 15-30% for adults aged ≥65 years [39]. Moreover, in previous studies on CKD patients, FT has a prevalence between 30% and 70% [22,[40][41][42][43][44]. Assuming that we are studying a population of subjects with CKD and that the primary endpoint is dichotomous (presence or absence of FT), we calculated an appropriate number of 137 patients when considering the lower limit of prevalence reported in the literature and 47 subjects when considering the upper limit of prevalence in the general and CKD population, respectively, taking into account a type I error of alpha 0.05 and a power of 80%.…”
Section: Participants (Eligibility Criteria)mentioning
confidence: 99%